2021
DOI: 10.31635/ccschem.020.202000443
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Catalytic Concise Synthesis of Hetero-3,3′-Bisoxindoles for the Construction of Bispyrroloindoline Alkaloids

Abstract: Asymmetric nucleophilic addition of 3-substituted N-Boc oxindoles to 3-bromooxindoles was designed to directly construct hetero-3,3′-bisoxindoles, with varying vicinal quaternary carbon stereocenters and N-substituents. The reaction progressed efficiently with high yields, good diastereo-and enantioselectivity (up to >99% ee) under mild reaction conditions catalyzed by chiral N,N′-dioxide/metal complexes. This methodology enabled the facile transformation of the generated hetero-3,3'-bisoxindoles into diverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 48 publications
(50 reference statements)
0
12
0
Order By: Relevance
“…[1][2][3][4][5][6][7] Construction of such highly substituted carbon centers is a difficult but important challenge due to a steric Page 1 of 19 CCS Chemistry 2 impediment for C-C bond formation, especially for controlling enantioselectivity. Although remarkable progress has been achieved in the catalytic enantioselective synthesis of quaternary stereocenters bonded by four carbon substituents, [1][2][3][4][5][6][7][8][9][10][11][12][13][14] the topic is still a long-term challenge in order to construct more interesting molecules.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Construction of such highly substituted carbon centers is a difficult but important challenge due to a steric Page 1 of 19 CCS Chemistry 2 impediment for C-C bond formation, especially for controlling enantioselectivity. Although remarkable progress has been achieved in the catalytic enantioselective synthesis of quaternary stereocenters bonded by four carbon substituents, [1][2][3][4][5][6][7][8][9][10][11][12][13][14] the topic is still a long-term challenge in order to construct more interesting molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Our research group focused on chiral Lewis acid catalysts of N , N ′-dioxides which are capable of a number of asymmetric transformations due to their easy preparation and structural modification. 14,15 It is anticipated that the stereo-environment created by the chiral Lewis acid could deliver to the bonded-aldehyde for asymmetric carbonyl catalysis, for instance, the asymmetric nucleophilic addition of the azomethine ylides, generated from picolinaldehyde and glycine ester ( Scheme 1c ). The study by Wang's group reported the utilization of metallated azomethine ylides in [3 + 2] cycloadditions with a variety of electron deficient alkenes.…”
Section: Introductionmentioning
confidence: 99%
“…As a continuation of our interest in asymmetric sulfur-chemistry, 14 we envisaged that chiral N , N ′-dioxide–metal complex catalysts 15 would be potentially useful in asymmetric addition of thiols to silyl glyoxylates, 16 although the reaction was found to be highly reactive in some solvents including water without catalysts. 11 a Herein we report an efficient enantioselective addition of silyl glyoxylates with various thiols as nucleophiles for the formation of chiral tertiary α-silyl alcohols containing a thiohemiketal skeleton ( Scheme 1b ).…”
Section: Introductionmentioning
confidence: 99%